Antimelanogenesis and Anti-Inflammatory Activity of Selected Culinary-Medicinal Mushrooms - Saad, Hazwani Mat; Sim, Kae Shin; Tan, Yee Shin (Begell House, 2018)
Five culinary-medicinal mushrooms are commonly available in the Malaysian market: Agaricus bispo-rus (white and brown), Ganoderma lucidum, Hypsizygus marmoreus, Pleurotusfloridanus, and P. pulmonarius. These species were selected for use in the current study, the aim of which was to investigate the antimelanogenesis and anti-inflammatory activity ofthese mushrooms in an attempt to evaluate their potential use in cosmeceuticals. Mushroom fruiting bodies were extracted with hot water, and the extracts were freeze-dried before testing. The antimelanogenesis activity of the extracts was determined by cell viability assay, measurement of intracellular melanin content, and cellular tyrosinase assay with B16F10 melanoma cells. The anti-inflammatory activity of the mushroom extracts was tested by measuring the levels of nitric oxide (NO), tumor necrosis factor (TNF)-a, and interleukin-10 excreted by RAW264.7 macrophages. Brown A. bisporus reduced intracellular melanin content to the largest extent-up to 57.05 ± 3.90%-without a cytotoxic effect on B16F10 melanoma cells. This extract also reduced cellular tyrosinase activity to 17.93 ± 2.65%, performing better than kojic acid, the positive control. In parallel, the extract from brown A. bisporus, at the highest concentration tested, has appreciable anti-inflammatory activity through reductions ofNO and TNF-a levels. The other 5 extracts showed moderate antimelanogenesis and anti-inflammatory activities. In summary, our findings show that A. bisporus (brown) extract has the potential to be used as an ingredient in whitening skincare products and to sooth the inflammatory response on the skin.